Identification of cuproptosis related subtypes and construction of prognostic signature in gastric cancer - Dong, Hao; Zhao, Shutao; Zhang, Chao; Wang, Xudong (Frontiers in Surgery, 2023)
Cuprotosis is a novel mechanism of cell death that differs from known mechanisms, which depends on mitochondrial respiration and is closely related to lipoylated components of the tricarboxylic acid (TCA) cycle. However, it is unclear whether cuprotosis-related genes (CRGs) affect the tumor microenvironment (TME) and prognosis of patients with gastric cancer. In this study, the genetic and transcriptional characteristics of CRGs in gastric cancer (GC) were analyzed, and five CRGs that were differentially expressed and correlated with the survival of patients were obtained. Two different molecular subtypes were identified according to the five CRGs. Then, we constructed a CRG_score that was applied to patients of any age, gender, and stage. Subsequently, we explored and found that cluster B and a high CRG_score had a worse prognosis, fewer immune checkpoints, and higher tumor immune dysfunction and exclusion (TIDE) compared to cluster A and a low CRG_score. In addition, two subtypes and the CRG_score were closely associated with clinicopathological characteristics, human leukocyte antigens (HLAs) and TME cell infiltration. A high CRG_score was featured with decreased microsatellite instability-high (MSI-H) and mutational burden. Meanwhile, the CRG_score was significantly related to the cancer stem cell (CSC) index and chemotherapeutic response. Moreover, we developed a nomogram to predict the survival probability of patients. Our study explained the role of CRGs in GC, and the prognostic signature could potentially provide an approach for personalized tumor therapy.